The time‐of‐day of myocardial infarction onset affects healing through oscillations in cardiac neutrophil recruitment - Schloss, Maximilian J; Horckmans, Michael; Nitz, Katrin; Duchene, Johan; Drechsler, Maik; Bidzhekov, Kiril; Scheiermann, Christoph; Weber, Christian; Soehnlein, Oliver; Steffens, Sabine (EMBO molecular medicine, 2016)
Myocardial infarction (MI) is the leading cause of death in Western countries. Epidemiological studies show acute MI to be more prevalent in the morning and to be associated with a poorer outcome in terms of mortality and recovery. The mechanisms behind this association are not fully understood. Here, we report that circadian oscillations of neutrophil recruitment to the heart determine infarct size, healing, and cardiac function after MI. Preferential cardiac neutrophil recruitment during the active phase (Zeitgeber time, ZT13) was paralleled by enhanced myeloid progenitor production, increased circulating numbers of CXCR2 hi neutrophils as well as upregulated cardiac adhesion molecule and chemokine expression. MI at ZT13 resulted in significantly higher cardiac neutrophil infiltration compared to ZT5, which was inhibited by CXCR2 antagonism or neutrophil‐specific CXCR2 knockout. Limiting exaggerated neutrophilic inflammation at this time point significantly reduced the infarct size and improved cardiac function. Synopsis Expression levels of chemokine receptor CXCR2 on circulating neutrophils exhibit diurnal oscillations. This causes time‐of‐day‐dependent variations in the number of neutrophils infiltrating the heart after myocardial infarction, with major consequences for infarction healing. During the sleep‐to‐wake transition period, myeloid progenitor production in the bone marrow is enhanced and the heart expresses higher levels of neutrophil chemoattractants and adhesion molecules. A myocardial infarction at this time point leads to excessive cardiac neutrophil recruitment, larger infarct size, and worsened heart function. The enhanced cardiac neutrophil infiltration after myocardial infarction onset during the sleep‐to‐wake transition period is CXCR2‐dependent. Graphical Abstract Expression levels of chemokine receptor CXCR2 on circulating neutrophils exhibit diurnal oscillations. This causes time‐of‐day‐dependent variations in the number of neutrophils infiltrating the heart after myocardial infarction, with major consequences for infarction healing.